Pemberdayaan Masyarakat Untuk Penyusunan Peraturan Desa Dalam Rangka Membangun Desa Sadar Hukum di Kabupaten Kampar - Andrikasmi, Sukamarriko; Musliadi, Ricki; Zulhidayat, Muhammad; Rozi, Fahrur (Journal of Community Engagement Research for Sustainability, 2025)
Riau University Faculty of Law's Merdeka Belajar Kampus Merdeka (MBKM) service program is an ambitious and far-reaching initiative, with the main goal of creating law-aware villages in three strategic locations: Ranah Baru Village, Batu Belah Village, and Naumbai Village. This initiative is not just an academic program, but also a transformative effort that aims to empower rural communities through improved legal literacy. As a concrete manifestation of MBKM vision, the program is comprehensively designed to improve legal understanding and awareness at the village level. With a holistic and sustainable approach, the program aims to create a community ecosystem that is not only law-abiding, but also has the capacity to identify, analyze, and resolve legal issues independently and equitably. Through a series of structured and directed activities, the program is expected to be a catalyst for significant social change. By improving the community's legal understanding, the program not only aims to reduce the potential for conflict and law violations, but also to build a strong foundation for sustainable and equitable village development. Ultimately, the envisioned law-aware village is expected to become a pilot model for the development of similar programs in other areas in Indonesia.